Weighted Minkowski distance-based differential protection for active distribution networks considering the uncertainty of frequency-domain characteristics - Jin, Wei; Li, Jian; Zhang, Shuo; Feng, Mengqiang; Feng, Shiguang (Frontiers in Energy Research, 2023)
With the increasing DGs (Distributed Generators) in the power system, the distribution network becomes more and more complicated. Because of the rapid change of DG output power and the diversity of DG location, it is difficult for the computing calculation of relay protection, bringing severe challenges to the current protection based on singleend electrical volume. Therefore, the double end-based protection is a good choice in view of the DG uncertainty and the network complexity. However, the power frequency offset after fault and the uncertainty of DG fault current results in uncertainty in the frequency domain characteristics, which can also negatively affect the differential protection. In view of this, a new differential protection method based on weighted Minkowski distance algorithm is proposed in this paper. First, the Minkowski distance algorithm is used to describe the similarity of the both current considering the uncertainty in the frequency domain characteristics. Second, each current similarity including the phase current, the positive current and the negative current is calculated separately to increase the protection sensitivity. Through the weighted algorithm distribution, the weight is assigned. Furthermore, a high-performance protection is designed to improve the protection sensitivity. This method is suitable for the active distribution network with different penetration rates of DGs and different types of DGs. The simulations show the proposed method with good feasibility and high superiority.